Analysis of Student Entrepreneurship decision making in the Learning Prerspective - Agus Syam; Sudarmi Sudarmi (Jurnal Ad'ministrare, 2019)
The main problem of entrepreneurship education in Indonesia is the mindset of most Indonesian people that the goal of continuing education to higher education to become a civil servant is not to be someone who has an entrepreneurial mentality. Entrepreneurship learning has not been able to change the mind-set of college graduates from finding jobs (job seekers) to creating jobs (job creators). Therefore, the formulation of the problem in this study is, "Is there an influence of entrepreneurial learning on student decision making in entrepreneurship at Makassar State University. This study aims to find out, "The effect of entrepreneurial learning on student decision making in entrepreneurship at Makassar State University. This research is an Explanatory Research with a Survey approach with a population of 654 Makassar State University students who propose a Student Creativity Program (PKM) with a sample of 242 which is done by proportional random sampling technique. Therefore, the formulation of the problem in this study is, "Is there an influence of entrepreneurial learning on student decision making in entrepreneurship at Makassar State University. This study aims to find out, "The effect of entrepreneurial learning on student decision making in entrepreneurship at Makassar State University. This research is an Explanatory Research with a Survey approach with a population of 654 Makassar State University students who propose a Student Creativity Program (PKM) with a sample of 242 which is done by proportional random sampling technique. The technique of collecting data uses observation, questionnaires, and documentation. Data analysis using SEM. The results of the study show; "There is a significant effect of entrepreneurial learning on student decision making in entrepreneurship at Makassar State University.